2006
DOI: 10.1002/ptr.1729
|View full text |Cite
|
Sign up to set email alerts
|

The evidence for clinical efficacy of rose hip and seed: a systematic review

Abstract: Moderate evidence exists for the use of a powder of the seeds and husks of a Rosa canina subspecies in patients suffering from osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 17 publications
1
53
0
1
Order By: Relevance
“…Two authors (CC and SC) extracted the data independently and evaluated the quality of the studies and the strength of the evidence of clinical effectiveness using the same criteria as in previous reviews , Gagnier et al, 2004, Chrubasik et al, 2006, 2007a,b, 2008, Vlachojannis et al, 2009, 2010a.…”
Section: Methodsmentioning
confidence: 99%
“…Two authors (CC and SC) extracted the data independently and evaluated the quality of the studies and the strength of the evidence of clinical effectiveness using the same criteria as in previous reviews , Gagnier et al, 2004, Chrubasik et al, 2006, 2007a,b, 2008, Vlachojannis et al, 2009, 2010a.…”
Section: Methodsmentioning
confidence: 99%
“…(2017) 14(2):1-8 doi:10.21010/ajtcam.v14i2.1 et al, 2010, 2011). In addition, other clinical trial reported that the antioxidant activity could contribute to the pharmaceutical effect of Rosa canina rose hips preparation (Chrubasik et al, 2006.…”
Section: Ferric Reducing Potentialmentioning
confidence: 99%
“…Rosehip has a particularly high vitamin C content compared with other fruits and vegetables (14,15), and contains other vitamins, minerals, sugars, fatty acids and flavonoids (14). Rosehip has traditionally been administered for the treatment of colds, infectious diseases and inflammatory diseases (16). In support of its traditional uses, various studies have reported that rosehip exhibited bioactivity, including antioxidant (17,18), anti-inflammatory (19)(20)(21)(22), hepatoprotective (23), anti-diabetic (17) and anti-obesity (24) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rosehip may be considered a functional food that promotes health. Although rosehip has traditionally been administered for treating uric acid (urate) metabolism disorders (16), its effects have not been characterized in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation